Carciniculture solid waste increases the morphophysiological characteristics of tomato seedlings (2021)
Appropriate waste handling is a concern in the fishing industry, seeking to minimize harm to the environment. This study aimed to evaluate vegetative growth at different concentrations of solid residue from shrimp farming in tomato seedlings. Tomato seeds cv. Santa Clara were sown in trays with substrate, until uniform germination and further development for transplant. The concentrations of the shrimp residue were mixed with coconut powder for use in the following treatments: coconut powder (control), 5, 10, 15 and 20 g of shrimp residue, with 8 replicates per treatment. After 7, 14, 21 and 28 days after transplant, the number of leaves and the length of the aerial part were evaluated. At the 50th day, the remaining phytotechnical, physiological and X-ray microanalysis characteristics were evaluated. The three parts of the solid residues were rich in macro and micronutrientes (Fe > Zn > Ca > S > P > Mn > Na > Mg > K > N). The plants grown with different concentrations of shrimp residue had a significant difference for the photosynthetic rate and transpiratory rate, starting at 10 g kg-1. The use of the P3 shrimp residue (cephalothorax + abdomen) was promising and could replace the use of fertilizers in the development of plants, reducing the amount of material released to the environment and easing degradation. The concentration of 10 g kg-1 of shrimp residue was efficient for the morphophysiological development of the tomato plants cv. Santa Clara.